2022
DOI: 10.3389/fpsyg.2022.834806
|View full text |Cite
|
Sign up to set email alerts
|

Incongruence in Lighting Impairs Face Identification

Abstract: The effect of uniform lighting on face identity processing is little understood, despite its potential influence on our ability to recognize faces. Here, we investigated how changes in uniform lighting level affected face identification performance during face memory tests. Observers were tasked with learning a series of faces, followed by a memory test where observers judged whether the faces presented were studied before or novel. Face stimuli were presented under uniform bright or dim illuminations, and lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Indeed, illumination can affect the amount and/or type of information gathered from faces, with impact on human visual processing, including colour perception (e.g., Shin et al, 2004;Kelber et al, 2017), visual acuity (e.g., Sheedy et al, 1984;Ferwerda, 1998;Hiraoka et al, 2015) and contrast sensitivity (e.g., Amesbury and Schallhorn, 2003;Alghwiri and Whitney, 2012;Wood, 2020). Consistently, studies on facial memory tests suggested an overall negative impact on face identification when illuminated by dimmer light (DiNardo and Rainey, 1989;Nyman et al, 2019;Lim et al, 2022). Moreover, lighting is accurately controlled in professional photography, different light effects are used to emphasize face properties in portraits (Arena, 2012), and specific methods are applied to manipulate and digitally correct the desired effects (Shu et al, 2017).…”
Section: Introductionmentioning
confidence: 90%
“…Indeed, illumination can affect the amount and/or type of information gathered from faces, with impact on human visual processing, including colour perception (e.g., Shin et al, 2004;Kelber et al, 2017), visual acuity (e.g., Sheedy et al, 1984;Ferwerda, 1998;Hiraoka et al, 2015) and contrast sensitivity (e.g., Amesbury and Schallhorn, 2003;Alghwiri and Whitney, 2012;Wood, 2020). Consistently, studies on facial memory tests suggested an overall negative impact on face identification when illuminated by dimmer light (DiNardo and Rainey, 1989;Nyman et al, 2019;Lim et al, 2022). Moreover, lighting is accurately controlled in professional photography, different light effects are used to emphasize face properties in portraits (Arena, 2012), and specific methods are applied to manipulate and digitally correct the desired effects (Shu et al, 2017).…”
Section: Introductionmentioning
confidence: 90%
“…More recently, another study systematically examined how changes in lighting between study and test affected face memory (Lim et al, 2022). Lighting was incongruent when faces were studied under bright lighting and then tested under dim lighting (Bright/Dim) and vice versa (Dim/Bright).…”
Section: Lightingmentioning
confidence: 99%